2016
DOI: 10.3389/fnbeh.2016.00065
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Safe Over Risky Options in Binge Eating

Abstract: Binge eating has been usually viewed as a loss of control and an impulsive behavior. But, little is known about the actual behavior of binging patients (prevalently women) in terms of basic decision-making under risk or under uncertainty. In healthy women, stressful cues bias behavior for safer options, raising the question of whether food cues that are perceived as threatening by binging patients may modulate patients’ behaviors towards safer options. A cross-sectional study was conducted with binging patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(101 reference statements)
1
10
0
1
Order By: Relevance
“…On the whole, however, the general pattern of responding on the BART in samples with subclinical binge eating behaviour has indicated greater levels of risk‐taking behaviour, which is in line with studies finding greater risk‐taking tendencies on other measures in populations with clinical levels of binge eating behaviour . In the present study, we therefore aimed to investigate whether participants with clinical levels of recurrent binge eating behaviour would indeed be found to exhibit greater risk‐taking tendencies on the BART given the greater sample size combined with a greater number of BART trials compared to previous investigations …”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the whole, however, the general pattern of responding on the BART in samples with subclinical binge eating behaviour has indicated greater levels of risk‐taking behaviour, which is in line with studies finding greater risk‐taking tendencies on other measures in populations with clinical levels of binge eating behaviour . In the present study, we therefore aimed to investigate whether participants with clinical levels of recurrent binge eating behaviour would indeed be found to exhibit greater risk‐taking tendencies on the BART given the greater sample size combined with a greater number of BART trials compared to previous investigations …”
Section: Introductionsupporting
confidence: 74%
“…Manasse et al, for example, found no differences on the BART between obese individuals with and without BED. Neveu et al found that individuals with BN tend to exhibit less risky behaviour in the BART following exposure to food vs neutral images but did not exhibit overall differences in behaviour compared to control participants. The study conducted by Neveu et al, however, was limited by low sample size, and the study conducted by Manasse et al administered only 10 trials in the BART, whereas the BART was originally validated across 30 trials of balloons with the same probability of explosion.…”
Section: Introductionmentioning
confidence: 99%
“…Across nine studies of AN, there was evidence of elevated IU and impaired decision‐making related to cognitive bias towards less risk in acute AN (Abbate‐Daga et al , ; Adoue et al , ; Frank et al , ; McFadden et al , ; Merwin et al , ; Moskovich, ; Neveu et al , ; Sternheim, Konstantellou, Startup, & Schmidt, ; Sternheim et al , ). Levels of IU in AN were higher than in OCD and psychosis, and similar to GAD (Sternheim, et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Of five studies of BN, some evidence of elevated IU was found (Celone, ; Frank et al , ; Giménez, ; Neveu et al , ; Sternheim, et al , ). However, there was inconsistent evidence of differences between AN and BN; similar levels to AN were found in one study (Frank et al , ) and lower levels in another (Sternheim et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…These processes facilitate a subsequent restriction of binge foods and reinforce binge occurrence [1]. These processes are i) the excessive food intake, which temporarily reduces the desire to eat these foods through a saturation effect [69]; ii) the use of planning and other cognitive control abilities during the binge to reduce long-term binge food attractiveness [10,11]; and iii) the overall feeling of loss of control at the end of the binge which is consecutive to the excessive food intake, feeling that strengthens subsequent binge food restriction [1]. …”
Section: Introductionmentioning
confidence: 99%